2015
DOI: 10.2217/fon.15.22
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targets in Glioblastoma

Abstract: Glioblastoma is the most lethal brain tumor. The poor prognosis results from lack of defined tumor margins, critical location of the tumor mass and presence of chemo- and radio-resistant tumor stem cells. The current treatment for glioblastoma consists of neurosurgery, followed by radiotherapy and temozolomide chemotherapy. A better understanding of the role of molecular and genetic heterogeneity in glioblastoma pathogenesis allowed the design of novel targeted therapies. New targets include different key-role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 140 publications
1
32
0
2
Order By: Relevance
“…In adults, components of the RTK/Ras/PI3K pathway are mutated in 88% of GBMs, those of the p53 pathway in 87%, and those of the Rb pathway in 78%. Mutations such as amplification of the epidermal growth factor receptor (EGFR) can be found in 45% of GBMs, gain of PI3K function in 15%, and loss of phosphatase and tensin homolog (PTEN) in 36% [23, 24]. These discoveries have led to a better understanding of the molecular signature of GBM and have revealed numerous consistent changes in genes and pathways [4, 16, 22, 25, 26].…”
Section: Glioblastoma Multiformementioning
confidence: 99%
See 2 more Smart Citations
“…In adults, components of the RTK/Ras/PI3K pathway are mutated in 88% of GBMs, those of the p53 pathway in 87%, and those of the Rb pathway in 78%. Mutations such as amplification of the epidermal growth factor receptor (EGFR) can be found in 45% of GBMs, gain of PI3K function in 15%, and loss of phosphatase and tensin homolog (PTEN) in 36% [23, 24]. These discoveries have led to a better understanding of the molecular signature of GBM and have revealed numerous consistent changes in genes and pathways [4, 16, 22, 25, 26].…”
Section: Glioblastoma Multiformementioning
confidence: 99%
“…The methylation status of MGMT (O 6 -methylguanine-DNA methyltransferase), a DNA-repair gene, is used as a GBM predictor because it is the major relevant biomarker for the response to temozolomide treatment [24]. Silencing of MGMT expression by promoter methylation impairs the ability of tumor cells to repair the DNA damage induced by temozolomide, further decreasing tumor cell survival [30].…”
Section: Current Standard Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The siRNAs-based RNAi technology has brought potential promises for patients to fight against this deadly disease by gene therapy approach (Gan et al, 2016). Great efforts have been made by the medicine research community to seek effective gene targets for treating glioblastoma and several strategies have been proposed and identified (Zorzan et al, 2015). In this study, anti-tumor therapeutics targeting TERT was employed as a unique therapy strategy due to the high prevalence of telomerase in most of the tumor cells (Ruden and Puri, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…GBs are classified as primary or secondary according to their formation [3,4]. The two GB types are characterized by different genetic alterations, and mutations in isocitrate dehydrogenase (IDH) genes are most commonly used to discriminate between primary and secondary GBs [5][6][7]. Many studies showed that IDH mutations are more frequent in secondary GB (>80%) than in primary GB (<5%) and that they correlate with a better prognosis [8,9].…”
Section: Introductionmentioning
confidence: 99%